Gender, politics, news a game of three sides - Ross, Karen 1957- (Wiley-Blackwell, 2017)
Gender, Politics, News: A Game of Three Sides explores the role of gender in the broader processes of political communication * The only contemporary book focusing on the relationships between gender, politics, and news media which takes a global perspective * An analysis of political journalism as a practice and the development of the field in terms of gendered workplace cultures * Offers a solid framework for understanding women s political representation, including real world case studies of women s campaigns for the top political job across a range of different geographies and contexts * Coverage of hot-button issues, such as political scandal and the role of new and social media in politics and elections, makes this a highly relevant and current work with resonances for a wide audience.